Efektivitas Model RICOSRE Berbantuan Lumio by SMART terhadap Kemampuan Pemecahan Masalah Matematis dan Resiliensi Matematis - Rosni Dwi Nurhayati; Eva Mulyani; Ike Natalliasari (Media Pendidikan Matematika, 2025)
This study aims to examine the effectiveness of implementing the RICOSRE learning model assisted by interactive media Lumio by SMART on students’ mathematical problem-solving skills and mathematical resilience, both partially and simultaneously, particularly on the topic of straight lines. This research is ekperimental research. The research employed a Quasi experimental design using a posttest-only control group design, with data collected through a problem-solving test and a mathematical resilience questionnaire. The population consisted of all eighth-grade students at SMP Negeri 14 Tasikmalaya, comprising eleven classes, and samples were selected through cluster random sampling to form two groups: an experimental class taught using the RICOSRE learning model assisted by Lumio by SMART, and a control class taught using the Problem-Based Learning (PBL) model assisted by PowerPoint. Data were analyzed using an independent samples t-test to examine partial effects and Multivariate Analysis of Variance (MANOVA) to assess simultaneous effectiveness. The results indicate that the RICOSRE learning model assisted by Lumio by SMART is effective in improving students’ mathematical problem-solving skills and mathematical resilience, both partially and simultaneously, suggesting its potential as an alternative technology-based instructional strategy to enhance the quality of mathematics learning. Keywords: RICOSRE, Lumio by SMART, mathematical problem-solving ability, mathematical resilience